2020
DOI: 10.1186/s13256-020-02562-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure as initial manifestation of conventional osteosarcoma rich in giant cells: a case report

Abstract: Background Osteosarcoma is a malignant tumor of the bone. The giant cell-rich osteosarcoma (GCRO) is a rare histological variant of the conventional osteosarcoma, accounting for 3% of all osteosarcomas. It has a variable clinical presentation, ranging from asymptomatic to multiple pathological fractures, mainly involving long bones, and less frequently the axial skeleton and soft tissues. Case presentation We present the case of a 25-year-old Hispanic woman, previously healthy, with a 1-month history of dyspn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the survival rate of primary osteosarcoma in pediatric spine is 18% at 5 years and 7% with distant metastasis[ 21 ]. However, gross total tumor resection should be attempted since it directly affects the prognosis[ 2 , 7 , 8 ]. A recent meta-analysis study also revealed the beneficial outcome after salvage surgery for residual primary spinal osteosarcoma[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for approximately 3% of osteosarcomas and mostly occurs in the long bones[ 5 ]. Spinal GCROs are extremely rare, with challenging diagnosis and management compared with long-bone GCRO[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 In contrast to long-bone GCRO, spinal GCRO is incredibly rare and poses unique challenges for its diagnosis and management. 8 Because of the difficulty in differentiating between its clinical, radiological and histopathological features, osteosarcoma of the spine is frequently initially misinterpreted as an aggressive benign vertebral lesion like osteoblastoma or aneurysmal bone cyst and can sometimes can be mistaken for chondrosarcoma or malignant giant cell tumour (GCT). 1 , 9 A biopsy is therefore usually indicated.…”
Section: Introductionmentioning
confidence: 99%